2018
DOI: 10.1101/446492
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reverse GWAS: Using Genetics to Identify and Model Phenotypic Subtypes

Abstract: Recent and classical work has revealed biologically and medically significant subtypes in complex diseases and traits. However, relevant subtypes are often unknown, unmeasured, or actively debated, making automatic statistical approaches to subtype definition particularly valuable. We propose reverse GWAS (RGWAS) to identify and validate subtypes using genetics and multiple traits: while GWAS seeks the genetic basis of a given trait, RGWAS seeks to define trait subtypes with distinct genetic bases. Unlike exis… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 79 publications
1
23
0
1
Order By: Relevance
“…Many whole-genome sequencing studies are underway in both large cohorts and smaller but more homogenous and deeply phenotyped subjects, and the value of these studies should be revealed over the next few years. Newer approaches, such as reverse phenotyping of subjects using genetic markers to define endotypes 77 and integrating of multi-omics measures using machine learning and other advance computational tools, are already becoming standard. Finally, there is still the need for finemapping studies at associated loci to pinpoint causal variants and the genes they regulate, as well as functional validation studies that link the effects of genetic risk and disease mechanisms to disease, which have been done thus far for surprisingly few asthma and allergic disease loci.…”
Section: Discussionmentioning
confidence: 99%
“…Many whole-genome sequencing studies are underway in both large cohorts and smaller but more homogenous and deeply phenotyped subjects, and the value of these studies should be revealed over the next few years. Newer approaches, such as reverse phenotyping of subjects using genetic markers to define endotypes 77 and integrating of multi-omics measures using machine learning and other advance computational tools, are already becoming standard. Finally, there is still the need for finemapping studies at associated loci to pinpoint causal variants and the genes they regulate, as well as functional validation studies that link the effects of genetic risk and disease mechanisms to disease, which have been done thus far for surprisingly few asthma and allergic disease loci.…”
Section: Discussionmentioning
confidence: 99%
“…Using RGWAS, Dahl et al 55 proposed a stress subtype in MDD, and identified three novel subtypes of metabolic traits. Using BUHMBOX (Breaking Up Heterogeneous Mixture Based On Cross-locus correlations), Han et al 56 found that seropositive and seronegative rheumatoid arthritis could be subdivided to form a new subgroup within seronegative-like cases.…”
Section: Minimal Phenotyping and Endophenotypes For Refining Psychiatmentioning
confidence: 99%
“…Microvascular dysfunction is well-recognized to associate with cardiometabolic disorders, including diabetes, hypertension, hyperlipidemia, and obesity. 1,2 Healthy microvascular networks achieve complex feats of traffic control: perfusing tissues spread throughout the body, avoiding hydraulic short circuits, and dynamically reallocating fluxes in response to tissue demands.…”
Section: Introductionmentioning
confidence: 99%